Permaculture Gamification as Innovative Learning Strategy to Enhance Students’ Collaboration Competency - Baharuddin, Rahmat; Saefudin, Saefudin; Kusnadi, Kusnadi; Najira, Najira; Zidan, Zuliande (FKIP Universitas Lampung, 2025)
Collaboration is a core competency to promote effective teamwork and prepare students for success in both academic and professional environments. Permaculture gamification learning has the potential to enhance students' collaboration competency. Permaculture is an artificial ecosystem that encourages sustainable agricultural practices. There is a noticeable gap in the literature on integrating gamification into permaculture learning to improve students' collaboration skills. Therefore, this study aims to investigate the students’ collaboration competency improvement through the application of permaculture gamification as a learning strategy on ecosystem topics. This study used a quantitative research method with nonequivalent (pretest and posttest) control-group design. There are experimental group and control group, both groups take a pretest and posttest but only experimental group receives the treatment. The sample in this study consisted of 50 students from one high school in the city of Bandung. The students in the control group followed the regular learning process in the classroom. Meanwhile, the students in the experimental group followed the permaculture gamification learning. The instruments used in this study were collaboration assessment tools, including self-assessment, peer assessment, and observation rubric. Statistical t-test applied to analyze di difference on students collaboration competency outcomes after treatment. The N-Gain value was calculated to evaluate the effectiveness of the treatment to improve students’ collaboration competency. The t-test results showed that there is a significant difference in students’ collaboration competency between the two groups (p = 0.04). Permaculture gamification learning significantly improved students’s collaboration competency (p < 0.05). Based on the N-Gain value, permaculture gamification learning has a higher impact on students’ collaboration competency (N-Gain = 0.56) compared to the regular learning strategy (N-Gain = 0.40). It can be concluded that permaculture gamification learning can effectively improve students’ collaboration competency. Keywords: permaculture gamification, collaboration competency, ecosystem.